A survey on prescription trends for hypertension in Faisalabad - Usman Sabir; Syed Ali Farhan; Ali Rashid; Junaid Ahmad; Saba Javed (AMMANIF, 2019)
High blood pressure or hypertension has been called the "silent killer", because it often has no warning signs or symptoms, and many people do not even know they have it. Over time, the constant pressure overload causes accumulating damage that eventually becomes more than your circulatory system can handle, often leading to serious health problems. Method: The present study is conducted to observe its prevalence in the city Faisalabad and its prescription trends by using retrospective method. The objective of this was to evaluate trends in prescription drug use among population living in the Faisalabad. Several hospitals in the area were visited for this article which includes DHQ, Allied Hospital, FIC and National hospitals. Results: The study explores which age group people, which gender is more prone towards this ailment. How lifestyle, diet and other factors affect blood pressure Moreover, it tells us how other diseases are interrelated with hypertension. It also provides information about the prescription trends of anti-hypertensive drugs. It elaborate that almost 47% male and 53% female are affected by this disease. Conclusion: Major cause of hypertension in female patients is angina and depression. Moreover, our data suggested that most of the outpatients with hypertension receive monotherapy and most frequently used class of drugs is the CCBs and ARBs. Studies showed that hypertension mostly coexist with heart diseases and other co-morbidities like diabetes. Any how the incidence of hypertension is dependent upon several factors like age, ethnicity, diet, and life style, environmental and physiological factors.